2020
DOI: 10.26421/jdi1.1-1
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Controlling Arrival Time to Prevent Late Arrival by Manipulating Vehicle Timetable Information

Abstract: Although it is socially and ethically important not to be late for a specified arrival time, late arrivals sometimes happen to people using public transportation. Although many methods aim to smooth a user's movement by providing useful information, there are few approaches to prevent late arrivals due to psychological factors. In this research, to make a user's arrival time earlier and thus prevent late arrival, we propose a method that manipulates time allowance by presenting information based on a psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…To induce health behavior, there is a step-logging competition application to improve daily walking motivation by competition progress modification based on the psychology of competition (Futami et al, 2021b) and a method to make users choose a healthy meal by presenting others' evaluations that are different from the actual ones (Takeuchi et al, 2014). There is a method of train timetable modification to prevent users' late arrival (Futami et al, 2019), an ambient display to encourage people to take the stairs instead of the elevator (Rogers et al, 2010), methods changing sightseeing routes and store rankings for each user to control tourist flow (Shen et al, 2016a,b). Other examples include an ambient light feedback method to encourage saving behavior such as power consumption (Lu et al, 2015), a presenting news trust indicators to inhibit spreading fake news in social media (Yaqub et al, 2020), and an interface to increase users' thoughtfulness in what they comment to others (Menon et al, 2020).…”
Section: Research Focusing On Psychological Phenomena and Cognitive B...mentioning
confidence: 99%
See 1 more Smart Citation
“…To induce health behavior, there is a step-logging competition application to improve daily walking motivation by competition progress modification based on the psychology of competition (Futami et al, 2021b) and a method to make users choose a healthy meal by presenting others' evaluations that are different from the actual ones (Takeuchi et al, 2014). There is a method of train timetable modification to prevent users' late arrival (Futami et al, 2019), an ambient display to encourage people to take the stairs instead of the elevator (Rogers et al, 2010), methods changing sightseeing routes and store rankings for each user to control tourist flow (Shen et al, 2016a,b). Other examples include an ambient light feedback method to encourage saving behavior such as power consumption (Lu et al, 2015), a presenting news trust indicators to inhibit spreading fake news in social media (Yaqub et al, 2020), and an interface to increase users' thoughtfulness in what they comment to others (Menon et al, 2020).…”
Section: Research Focusing On Psychological Phenomena and Cognitive B...mentioning
confidence: 99%
“…In terms of designing information presentations systems that may affect a user's cognition and psychology, many recent studies have shown that it is necessary to clarify the existence and manipulation methods for unconscious phenomena caused by information presentation (e.g., psychological effects, illusions, and cognitive biases) (Adams et al, 2015;Kim et al, 2016;Costa et al, 2018;Futami et al, 2019;Komatsu and Yamada, 2020). For example, some studies have focused on information presentation systems for heart rate sensors (Costa et al, 2016(Costa et al, , 2017(Costa et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also focused on information presentation elements that cause psychological effects. There is a bus timetable presentation method that modifies bus departure time intervals to induce the user's psychology and behavior to accept arriving early and waiting at the bus stop so as not to miss the bus [71]. There is a method of presenting a lie in the remaining strength gauge to design behavior in the game [72].…”
Section: B Techniques For Manipulating Illusions Psychological Effect...mentioning
confidence: 99%
“…Takeuchi et al [ 44 ] showed that others’ evaluations (e.g., likes) of user’s meal contents affect user’s meal choices and taste preferences, then they proposed a method to make users choose a healthy diet by presenting others’ evaluations that were different from the actual ones. Futami et al proposed a method to manipulate walking motivation caused by competition progress information of step count logs [ 45 ] and a method to induce the behavior of not missing the train by showing the train timetable in an ingenious way [ 46 ]. Suzuki et al [ 47 ] proposed a method to improve the output of collaborative work over online video communication by changing the facial expressions of dialogue partners from the actual ones.…”
Section: Related Researchmentioning
confidence: 99%